The factor that contributed to the effectiveness of the training program that conducted by SIRIM Berhad / Noridani Masani - Masani, Noridani (Faculty of Business and Management, 2010)
This research provides an analysis and evaluation of the factors that contribute to the effectiveness of the training program that provided by SIRIM Berhad. Methods of analysis include primary and secondary data. The primary data include the questionnaire and interview. In this research, the 60 set of question was been given to the respondent. For the secondary the methods that are used is journals, website, article, books and newspaper. The main objectives, is to evaluate the most factors that contribute to the effectiveness of training program conducted by the SIRIM Berhad based on the respondent’s feedback arising from the training. Based on the result, the trainee or respondent are satisfied with the implementation on program. This is including venue and surrounding, schedule and time of period, food and drinks provided. The implementation on program have a strong significant with training effectiveness compare to others factors. Besides that, this report also finds that the respondents of the training program said they are not satisfied with the objectives and content in the training program. These factors are low significant with training effectiveness compare to others factors. The conclusion, the management should provide the objectives and content provide the clear, appropriate and suitable objectives that also relate with the goals of the company so that can make trainer feel satisfied and more interested to attend the training program. The trainee or respondent also feel force to attend the training. This is because, when they do not attend the training, it will affect their promotion or performance. So, the trainee attends the training without know the objectives of the training program. Next, organization also needs to choose the right content that relate with the scope of the work. Besides that, the content during training also should make the respondent are interested to attend the training program. So, the trainee or respondent not feel very bored and trainer can adopt the content with the real situation of work because they are concentrating with the content.